Revolutionary challenges of the Myanmar Generation Z students and the impact on the rapidity of the 2021 spring revolution - Thein, Kyawt Nandar Myo; Nugroho, Kris; Aminah, Siti (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
The Generation Z student revolutions in Myanmar that fight for democracy against the military coup in 2021 present challenges that limit the rapidity of the revolution. The research aims to explore Generation Z students' movements and challenges in anti-coup protests, armed struggle movements, and click movements as well as the impacts on the rapidity of the revolution. The study used a qualitative method by applying the social movement theory and revolutionary concept of Charles Tilly which reveal that Generation Z students are confronted with deaths triggered by violent crackdowns, illegal arrests, and imprisonment, difficulties with the environment and livelihoods, financial matters, weaponry issues, and internet outages in conducting movements against the coup. Challenges, however, simply dragged down the protest movement's rapidity; armed movements and online click movements are still escalating on their own rapidity. The research concludes that the outcome of the revolutionary movement is unpredictable except the conflict between the military and armed resistance is gradually expanding day by day during a two-and-a-half-year post-coup period.